O65: C-MET PROTEIN AS A COLORECTAL CANCER BIOMARKER FOR FLUORESCENCE IMAGE-GUIDED SURGERY. (27th April 2021) - Armstrong, G; Portal, C; Khot, MI; West, NP; Maisey, T; Perry, S; Tolan, D; Jayne, DG
Abstract: Introduction: The c-Met transmembrane protein is vital for cell differentiation and migration and is overexpressed in many gastrointestinal cancers. This study aimed to investigate a novel c-Met targeted peptide coupled to a fluorophore (EMI-137, Edinburgh Molecular Imaging Ltd.) for use in fluorescence image-guided colorectal cancer (CRC) surgery. Method: A high c-Met expressing cell-line, HT29, was identified with temporary RNA suppression and used to develop a mouse xenograph CRC model. Tumours were allowed to grow to 10mm. EMI-137 was injected into the tail vein and biodistribution analysed using the IVIS system. Nine patients undergoing elective surgery for colon cancer received a single IV dose EMI-137 1-3 hours before surgery. Tumour and LN fluorescence was assessed with a prototype Karl Storz laparoscope. Intraoperative fluorescence was correlated with radiological and pathological TNM stage and tissue c-Met expression using immunohistochemistry. Result: The HT29 xenograph CRC model demonstrated selective EMI-137 uptake and fluorescence 1- 6 hours post administration. Nine participants aged 67-77 years received EMI-137 106 minutes (S.D±17) before surgery. Marked background fluorescence was observed in all patients. 4/9 (44%) patients showed mild increase in tumour fluorescence over background. 5/9 patients had histological LN disease, but no fluorescent nodes were detected intraoperatively. There was no correlation with T-stage. At histopathological assessment 8/9 participants showed moderate or high tumour c-Met expression. 8/8 malignant LNs demonstrated high c-Met expression. Conclusion: EMI-137 is specific for human c-Met in 2D and xenograph CRC models. EMI-137 is safe for human use but its utility is limited by insufficient tumour-to-background ratios. Take-home message: This first-in-man study of a novel fluorescent peptide targeted to the c-Met receptor, found EMI-137 lacked the sensitivity and specificity to accurately map the tumour margins and lymph node burden in laparoscopic colonic cancer resection surgery.